2011
DOI: 10.21608/ajs.2011.14666
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Strawberry Grown in Root- Knot Nematode Infested Soil Under Different Safety Control Applications

Abstract: Two successive field experiments during two seasons of 2008 and 2009, were carried out to evaluate some safety treatments including: mulching, tunnels, natural yeast extract, antioxidant and two rhizobacteria Serratia marcescens and Pseudomonas fluorescens towards root-knot nematode Meloidogyne spp. on strawberry plant grown in naturally infested soil and consequently their probable effects on growth parameters, chemical components and yield of strawberry compared to untreated control. Results of this study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another investigation revealed that the administration of Bacillus subtilis and Psedomonas putida, both separately and together, dramatically increased the activity of superoxide dismutase, peroxidase, and catalase against RKN (Singh & Gaur, 2017). Mahdy and Sally (2011) reported that strawberries cultivated in RKNs-infested soil exhibited elevated peroxidase activity when compared to untreated plants. Also, it is well recognized that PGPR modifies plant metabolite levels by raising the enzymatic activities of secondary metabolites, including organic acids, sugars, amino acids, and phenols (El-Rahman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation revealed that the administration of Bacillus subtilis and Psedomonas putida, both separately and together, dramatically increased the activity of superoxide dismutase, peroxidase, and catalase against RKN (Singh & Gaur, 2017). Mahdy and Sally (2011) reported that strawberries cultivated in RKNs-infested soil exhibited elevated peroxidase activity when compared to untreated plants. Also, it is well recognized that PGPR modifies plant metabolite levels by raising the enzymatic activities of secondary metabolites, including organic acids, sugars, amino acids, and phenols (El-Rahman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticulture technologies proved effective against PPNs in Egypt. Reduction in number of RKN galls, egg masses, females/root system, and number of J 2 /250 g soil was attained with enhanced strawberry fruit quality and quantity (Mahdy and Midan 2011). Five different colored polyethylene sheets (transparent, red, black, green, and blue) were used to cover the naturally infested soil as a solarization and post-planting mulch.…”
Section: Common Cultural Practices In Egyptmentioning
confidence: 99%
“…In other words, plants infection by a pathogen alters the activity of oxidizing and hydrolyzing enzymes (Mohammadi and Kazemi, 2002). Several reports exist regarding the association between increased activities of oxidizing enzymes, especially PROX (Rani et al, 2008;Arun et al, 2010;Mahdy and Sally, 2011;Anjum et al, 2012). Usually, the activities of these enzymes in the infected resistant tissues are more than infected tissues of susceptible cultivars (Sankar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%